Lessons from the Trenches: Special Education Service Delivery and Instruction Amidst the COVID-19 Health Crisis in California Schools - Nicholson, Nicole (Journal of the American Academy of Special Education Professionals, 2022)
In this qualitative study, 8 mild/moderate education specialists in California were interviewed to discuss what lessons were learned regarding online instruction and service delivery for students receiving special education services when schools closed due to the COVID-19 health crisis. Thematic analysis indicated that the following strategies were successful and would continue to be used or eventually implemented: Addressing affect before academics, frequent face to face interactions with students online, using familiar technology with flexibility, and creating consistency between home and school routines. Giving asynchronous assignments and nonconsequential attendance and evaluation were considered ineffective practices posing major barriers impacting instruction and special education service delivery.